Younger poor ovarian response women achieved better pregnancy results in the first three IVF cycles. Issue 5 (May 2016) - Yang, Yajuan; Sun, Xiuhua; Cui, Linlin; Sheng, Yan; Tang, Rong; Wei, Daimin; Qin, Yingying; Li, Weiping; Chen, Zi-Jiang
Abstract: This retrospective cohort study observed the live birth rates as well as cumulative live birth rates in women with poor ovarian response (POR) undergoing IVF–embryo transfer treatment, stratified for age and cycle number. Four hundred and one patients with POR diagnosed according to the Bologna criteria were enrolled and 700 IVF–ET cycles were analysed. The overall live-birth rate per cycle was 18.3%. From cycle 1 up to cycle 3, the live-birth rates decreased significantly from 22.2% to 11.1%. The live-birth rate fell to 2.4% in cycles 4 and over. When age advanced, the live birth rates decreased obviously ( P < 0.01): 30.0% for women <35 years old, 17.0% for those 35–40 years old, and 9.0% for women older than 40 years. Similarly, the cumulative live birth rates dropped from 48.0% (<35 years) to 16.9% (≥40 years) accordingly. Younger patients (<35 years old) with POR achieved better pregnancy results compared with patients of advanced age. Extremely low live-birth rates could be anticipated after three unsuccessful cycles; therefore it may not be appropriate to suggest more IVF cycles in POR women.